1985
DOI: 10.1001/jama.1985.03360020085030
|View full text |Cite
|
Sign up to set email alerts
|

Some Current Issues Relating to Rubella Vaccine

Abstract: At the time of licensure in 1969, available data indicated that rubella vaccines were safe, noncommunicable, and effective. Since vaccine virus could cross the placenta and infect the fetus, cautious use of the vaccines in childbearing-age women was recommended. Over the past 15 years, additional information about the vaccines has been accumulated. This article provides an update of data on (1) the risk and degree of joint symptoms following vaccination and revaccination, (2) the duration of vaccine-induced im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Although the observed risk of congenital malformations after rubella vaccination with RA 27/3 is zero, the theoretical risk may be as high as 1P6% ( Table 2). The risk is substantially less than the estimated 20-50% risk of CRS associated with natural rubella infection of women during the first trimester of pregnancy [12]. Reasonable precautions, however, should still be taken to preclude vaccination of pregnant women, including asking women if they are pregnant, excluding those who say they are, and explaining the theoretical risks to the others.…”
Section: Vaccination Of Women Of Childbearing Agementioning
confidence: 93%
“…Although the observed risk of congenital malformations after rubella vaccination with RA 27/3 is zero, the theoretical risk may be as high as 1P6% ( Table 2). The risk is substantially less than the estimated 20-50% risk of CRS associated with natural rubella infection of women during the first trimester of pregnancy [12]. Reasonable precautions, however, should still be taken to preclude vaccination of pregnant women, including asking women if they are pregnant, excluding those who say they are, and explaining the theoretical risks to the others.…”
Section: Vaccination Of Women Of Childbearing Agementioning
confidence: 93%
“…However, a study of 321 women who had received the rubella vaccine 3 months before or after conception revealed no congenital malformations compatible with congenital rubella infection. 26 Immunization is also contraindicated in immunosuppressed patients, although it can be administered to individuals with asymptomatic HIV infection as well as to persons with mild immunosuppression. In healthy individuals, minor illnesses with or without fever are not a contraindication to vaccination.…”
Section: Currently Licensed Vaccines Virusesmentioning
confidence: 99%
“…64 These joint symptoms typically begin within the first 3 weeks after vaccination and remit within 11 days. 26 The knees and the fingers are most frequently involved, but any joint may be affected. 63 Hepatitis A virus.…”
Section: Currently Licensed Vaccines Virusesmentioning
confidence: 99%
“…Clinical studies showed that rubella vaccine induced antibodies at lower levels than those produced bella-like symptoms. The most troublesome of these were arthralgia and arthritis [17]. These were uncommon in children by the natural disease.…”
Section: S141mentioning
confidence: 99%
“…U.S. recommendations. The U.S. recommendations atprotect the fetus, even in the presence of reinfection [17]. However, some thought otherwise, and this issue was a subject tempted to achieve epidemic control by large-scale immunization programs in children aged §1 year to puberty.…”
Section: S141mentioning
confidence: 99%